The role of imitation innovations in entrepreneurship development - Mamatov Olimjon ugli, Abdurauf (THE INNOVATION ECONOMY, 2024)
This article describes the conditions and features of the use of imitation innovations in small businesses in Uzbekistan. The advantages of imitation innovations are also highlighted. Using certain integral indicators, the level of development of the economic and scientific potential of the regions was analyzed, and the possibilities for innovative development of entrepreneurship in the regions were identified. The article reflects that when carrying out independent innovation, research, development and technological work is carried out by the enterprise itself, and this is very risky and requires large financial costs. Typically, large companies engage in independent innovation activities. The researcher investigated that with imitation innovation, an enterprise directly purchases advanced technologies and equipment and carries out work aimed at their modernization and improvement. Research carried out within the framework of imitation innovations is free from risk and repeated research, high costs (upgrading a new technology is cheaper compared to developing a new technology), goods and technologies that have found their place in the market are imitated. The article is devoted to the place and role of imitation innovations in the development of entrepreneurship, analytical tables are presented by region.